Si Interlayer Thickness Dependence of Hysteresis Loop in Co/Si/Co/GaAs(001) - Islam, J.; Yamamoto, Y.; Shikoh, E.; Fujiwara, A.; Hori, H. (Journal of Scientific Research, 2012)
Magnetic hysteresis loop changes from two-phase to single-phase with decreasing Si interlayer thickness in Co/Si/Co/GaAs. Coercive field of 50 nm Co deposited on Si layer decreases with the increase of Si interlayer thickness. Deposition of Au layer between Co and Si changes the magnetic hysteresis loop. We propose that the formation of cobalt silicides at the interface of Co and Si modulate magnetic properties of the trilayer without Au buffer layer. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10852 J. Sci. Res. 4 (3), 561-567 (2012)